Nano-Disperse Borides and Carbides: Plasma Technology Production, Specific Properties, Economic Evaluation; IOP Conference Series: Materials Science and Engineering; Vol. 125 : Materials Treatment: Current Problems and Solutions - Galevskii G. V.; Rudneva V. V.; Galevskii S. G.; Tomas K. I. Konstantin Iosipovich; Zubkov M. S. (2016, 2016)
Title screen